2020
DOI: 10.1111/jnc.15253
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tau‐induced phenotypes by vitamin E demonstrates the dissociation of oxidative stress and phosphorylation in mechanisms of tau toxicity

Abstract: Various lines of evidence implicate oxidative stress in the pathogenic mechanism(s) underpinning tauopathies. Consequently, antioxidant therapies have been considered in clinical practice for the treatment of tauopathies such as Alzheimer's disease (AD), but with mixed results. We and others have previously reported increased protein oxidation upon expression of both human 0N3R (hTau 0N3R ) and 0N4R (hTau 0N4R ) tau in vivo. Building on these studies, we demonstrate here the suppression of hTau 0N3R associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Vulnerability to oxidative stress has been employed as a measure of tau accumulation-dependent toxicity in tauopathies including Alzheimer’s disease [ 44 , 45 ] and has been modeled in Drosophila [ 32 , 33 , 46 , 47 ]. Hence, the resistance of adult hTau expressing flies and controls to 5% H 2 O 2 was assessed as before [ 32 , 33 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vulnerability to oxidative stress has been employed as a measure of tau accumulation-dependent toxicity in tauopathies including Alzheimer’s disease [ 44 , 45 ] and has been modeled in Drosophila [ 32 , 33 , 46 , 47 ]. Hence, the resistance of adult hTau expressing flies and controls to 5% H 2 O 2 was assessed as before [ 32 , 33 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in another meta-analysis, it has been reported that a low concentration of serum vitamin E is associated with AD [ 105 ]. Moreover, substantial evidence suggested that vitamin E successfully suppresses tau-induced neurotoxicity in Drosophila [ 106 , 107 , 108 ]. In one of the recent studies, it is proposed that vitamin E has significantly reduced oxidative and nitrosative damage in AD [ 109 ].…”
Section: Role Of Antioxidants In Alzheimer’s Diseasementioning
confidence: 99%
“…For instance, in AD-like models based on metabolic dysfunction and redox imbalance, L-carnitine has been shown to exert neuroprotective effects through mechanisms involving both the enhancement of cell metabolism and the improvement of antioxidant defenses [ 203 ]. Likewise, since reduced concentrations of different forms of vitamin E have been observed in AD patients compared to healthy controls [ 204 ], treatments with vitamin E have been considered to overcome oxidative damage and neuronal degeneration [ 205 , 206 , 207 ], and to reduce the risk of developing AD [ 208 , 209 ]. However, most of the clinical trials examining the efficacy of vitamin E treatment have yielded uncertain results in delaying or halting the onset and the progression of AD [ 210 , 211 , 212 , 213 ].…”
Section: Ros and Antioxidants In Neurodegenerative Diseasesmentioning
confidence: 99%